Pengaruh Perilaku Menyimpang Pengguna Tinder Terhadap Citra Aplikasi Kencan Tinder - Kusuma, Satria Kusuma; Letare, Yolanda Natasia (Jurnal InterAct, 2022)
The massive growth of online dating application fascinates anyone who have an interest to make acquaintances and find partner especially for young people. However, there are negative effects of using online dating application, among others are sexual harassment, identity fraud, rape, and even murder. The study aims to discover the effects of deviant behavior toward image building of Tinder dating application in the eyes of the consumers. The theories used in the study were communication theory, corporate communication, deviant behavior, image and new media. Indicator of X variable in the study was deviant behavior category which had three dimensions namely nonconform action, antisocial action, and criminal action. Meanwhile the indicator for Y variable in the study was individual image toward stimulant which had four dimensions namely perception, cognitive, motivation, and attitude. The study used quantitative method in which questionnaires were randomly distributed to 100 respondents. The result of the study is deviant behavior has strong, negative and significant effects toward the image building of application in the eyes of consumers.